THE ANALYSIS AND MODEL OF IMPLEMENTATION CORPORATE SOCIAL RESPONSIBILITY BASED ON CARROLL’S PYRAMID (A Case Study on PT. Perusahaan Gas Negara (Persero) Tbk) - Rintami, Aruma Resdha (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
PT. Perusahaan Gas Negara (Persero), Tbk. is the largest national company in the natural gastransmission and distribution segment. Most of the main goal of a company is to gain maximumprofit, however, it is not always in line with the society and environmental requirements thatcan cause damage to society and surrounding environment. Therefore, this research aims toanalyze the implementation of corporate social responsibility at PT. Perusahaan Gas Negara(PERSERO), Tbk. in 2016 and 2017 based on Carroll’s Pyramid. This research is a qualitativeresearch and conducted using case study method and literature study. The result of this researchis the implementation of Corporate Social Responsibility at PT. Perusahaan Gas Negara(PERSERO), Tbk. fulfilled the concept of Carroll’s pyramid in economic responsibility ingaining profit as their foundation of the company activities. In terms of legal responsibility,PT. PGN carried out the CSR activities based on the applicable law, therefore, it is free fromthe penalties. Moreover, in terms of ethical responsibility, PT. PGN conducted the CSRactivities based on the unwritten norms, regulation and as expected by the stakeholder. The toplevel of the pyramid is philanthropic responsibility, CSR activities of PT. PGN implementedits’ responsibility to the stakeholder without expecting rewards.Keywords: Corporate Social Responsibility, Carroll’s Pyramid, Profit, Social, Environment